Radiofrecuencia convencional y pulsada armonizada en el ganglio de Gasser para el tratamiento de la neuralgia del trigémino: resultados del protocolo Dolomedic - Francisco Javier Machuca Vigil; Rafael Orlando Vallejo Estrella; Roberto Jameson Rosales; Francesca Dolciami; Eduardo Perez Lozano (Critical Care & Emergency Medicine, 2026)
Objectives: To describe the experience with the Dolomedic protocol, which combines conventional radiofrequency (CRF) and harmonized pulsed radiofrequency (PRF) of the Gasserian ganglion, for the treatment of refractory trigeminal neuralgia. Material and Methods: A retrospective study was conducted in 77 patients with unilateral type 1 and 2 trigeminal neuralgia treated between July 2020 and July 2025 at Dolomedic Alta Especialidad (Heroica Matamoros, Mexico). The percutaneous approach to the Gasserian ganglion was performed under fluoroscopic guidance, applying a sequential protocol that integrates sublesive PRF (44 °C, 440 s, 40 ms, 4 Hz), escalated CRF (60–70 °C, 440 s) and a second PRF cycle. All patients received perineural dexamethasone. Clinical characteristics and pain evolution were assessed using the visual analogue scale (VAS) in the preoperative period and up to 60 months of follow-up. Results: The sample included 53 women (68.8%) and 24 men (31.2%). The most frequent etiology was neurovascular compression (67.5%), followed by structural lesions (23.4%) and idiopathic cases (9.1%). The most frequently involved branches were V2 (44.2%) and V3 (40.3%). Baseline VAS was ≥ 8 in all groups. After the intervention, a significant reduction was observed, with VAS ≤ 2 from the first month, maintained throughout follow-up in both sexes, all etiologies and affected branches. Mild and transient adverse effects were reported: facial paresthesias in 18 patients and intraoperative bradyarrhythmia in 9, resolved without sequelae. No major complications were observed. Conclusions: The combination of CRF and harmonized PRF is an effective and safe technique for the treatment of refractory trigeminal neuralgia, with sustained pain control up to five years and a low incidence of adverse effects.